(untitled) (Leadership, Education, Personality: An Interdisciplinary Journal, ISSN: 2524-6178, 2025)
The increasing environmental deterioration, driven by rapid economic growth, consumption patterns and technological advancements, has raised concerns about sustainability. Consumers are becoming more environmentally aware, influencing their purchase intentions and driving a shift towards green products. Marketers have also responded by integrating eco-friendly products into their offerings to meet evolving consumer demands. This study explores the key factors influencing green purchase intention, including environmental concern, pricing and promotional strategies. A survey was conducted with 138 respondents from the Rohtak district of Haryana, using a structured questionnaire. Data analysis using Exploratory Factor Analysis (EFA) identified three major factors affecting consumer green purchase behavior: environmental concern, price sensitivity and promotional influence. The findings indicate that environmental concern is the most significant driver, followed by price considerations and promotional efforts. Consumers are more inclined to purchase green products if they perceive a direct environmental benefit, but pricing and marketing communication also play crucial roles in shaping purchase behavior. This study highlights the need for marketers to emphasize environmental benefits, ensure competitive pricing and develop effective promotional campaigns to enhance green product adoption. Future research should explore long-term sustainability strategies, assess the effectiveness of eco-marketing campaigns and investigate consumer behavior shifts towards sustainable consumption.